GENETIC DIVERSITY ANALYSIS IN CHILLI (CAPSICUM ANNUUM L.) USING RAPD MARKERS - J. V. BAHURUPE,; S. B. SAKHARE,; P. L. KULWAL,; A. A. AKHARE,; B. D. PAWAR, (The Bioscan, 2013)
Genetic diversity in 23 chilli genotypes was analyzed by RAPD markers of the 13 random primers used 9 were polymorphic. The amplification profile of these 9 primers consisted of 63 fragments used with size ranging from 391 bp to 2754 bp of which 35 were monomorphic and 28 were polymorphic with 44.4 % polymorphism. The number of bands generated by each primer varied from 5 (OPB-10) to 9 (OPB-01 and OPB-15) with an average of 7 fragments per primer. The percentage of polymorphic bands with different primers ranged from 14.29 to 66.67 %. The similarity coefficients detected by RAPD marker ranged from 0.42 to 0.97 which revealed existence of genetic variation among chilli genotypes. The consensus tree constructed showed three major clusters. First cluster comprised of 13 genotypes, second cluster of 7 genotypes and third cluster of 3 genotypes. The RAPD technology proved useful in describing genetic diversity among chilli genotypes.